Electroadhesion between a flat touchscreen and the human finger with randomly self-affine fractal surface - M. Feshanjerdi (Friction)
Abstract In this study, the effects of finger roughness on the electrostatic potential, electrostatic field, and average effective squeezing pressure between a human finger and a touchscreen are calculated by the perturbation method. This theory is an extension of an earlier work by Persson. It is found that an additional potential <ϕ (2)> will appear between the solids when the roughness effect is considered in calculating the perturbation potential. This additional potential is still proportional to the distance ū from the bottom surface. Therefore, the effect of the roughness increases the effective potential <ϕ> between the two solids. As a result, the average electrostatic field and average effective squeezing pressure increase. Using the increased effective squeezing pressure, we obtain the contact area, average surface separation, and friction between a human finger and the surface of a touchscreen. The effect of the roughness of the finger skin on the increased average effective squeezing pressure (electroadhesion) increases the contact area and reduces the average surface separation between the finger skin and touchscreen. Therefore, the finger-touchscreen friction increases. The surface topography for the forefinger skin is also measured by atomic force microscopy to obtain more realistic results. The auto spectral density function for the forefinger skin surface is calculated as well.